Embryology of the Orbit - Cho, Raymond I.; Kahana, Alon (Journal of Neurological Surgery Part B: Skull Base, 2021)
The orbit houses and protects the ocular globe and the supporting structures, and occupies a strategic position below the anterior skull base and adjacent to the paranasal sinuses. Its embryologic origins are inextricably intertwined with those of the central nervous system, skull base, and face. Although the orbit contains important contributions from four germ cell layers (surface ectoderm, neuroectoderm, neural crest, and mesoderm), a significant majority originate from the neural crest cells. The bones of the orbit, face, and anterior cranial vault are mostly neural crest in origin. The majority of the bones of the skull base are formed through endochondral ossification, whereas the cranial vault is formed through intramembranous ossification. Familiarity with the embryology and fetal development of the orbit can aid in understanding its anatomy, as well as many developmental anomalies and pathologic conditions that affect the orbit.
Keywords: orbit; skull base; embryology; neurulation; optic vesicle; neural crest; neurocristopathy